Human Resource Capacity Challenges in Village Information System Implementation: Tantangan Kapasitas Sumber Daya Manusia dalam Implementasi Sistem Informasi Desa - Pramesswary, Ikko Della; Rodiyah , Isnaini (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Digital governance has become a strategic instrument in strengthening transparency and public services at the village level in Indonesia. Specific Background: The Village Information System (SID) was introduced to support data management and administrative services; however, its utilization in many villages remains limited. Knowledge Gap: Existing studies largely focus on technical implementation or community response, while in-depth analysis of village officials’ human resource quality remains underexplored. Aims: This study aims to examine the quality of village apparatus human resources in implementing SID in Gemurung Village, Sidoarjo Regency, using indicators of knowledge, skills, and abilities. Results: The findings show that village officials generally understand SID functions, yet their knowledge and digital mastery are not optimal due to limited training and educational mismatch. Skills related to innovation and creativity are still low, as SID usage is confined to basic features. Nevertheless, SID supports accurate data processing and informed decision-making. Novelty: This study offers a human resource–centered perspective on SID implementation at the village level. Implications: Strengthening continuous training and digital capacity building is essential to optimize SID utilization and improve village governance.